2016
DOI: 10.1155/2016/8905365
|View full text |Cite
|
Sign up to set email alerts
|

Innate Immune Response of Human Embryonic Stem Cell‐Derived Fibroblasts and Mesenchymal Stem Cells to Periodontopathogens

Abstract: Periodontitis involves complex interplay of bacteria and host immune response resulting in destruction of supporting tissues of the tooth. Toll-like receptors (TLRs) play a role in recognizing microbial pathogens and eliciting an innate immune response. Recently, the potential application of multipotent stem cells and pluripotent stem cells including human embryonic stem cells (hESCs) in periodontal regenerative therapy has been proposed. However, little is known about the impact of periodontopathogens on hESC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 60 publications
(77 reference statements)
1
19
0
1
Order By: Relevance
“…The expression of surface markers (CD73, CD90, and CD105), data from gene expression analysis, and Alizarin Red and immunofluorescent staining demonstrate the osteogenic commitment and differentiation potential of these GFP-expressing hESCs. These results are in agreement with previous studies [10, 15, 20, 34, 35]. These data also suggest the stable expression of GFP in hESC-OPs and the genetic manipulation did not affect their osteogenic differentiation.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The expression of surface markers (CD73, CD90, and CD105), data from gene expression analysis, and Alizarin Red and immunofluorescent staining demonstrate the osteogenic commitment and differentiation potential of these GFP-expressing hESCs. These results are in agreement with previous studies [10, 15, 20, 34, 35]. These data also suggest the stable expression of GFP in hESC-OPs and the genetic manipulation did not affect their osteogenic differentiation.…”
Section: Discussionsupporting
confidence: 93%
“…Jeon et al used a biomimetic approach to regenerate bone by 3D coculture of human PSC-derived osteoblasts and osteoclasts within a synthetic scaffolds [46]. We have recently developed protocols to direct the differentiation of hESCs to vascular cells [20, 47]. In future studies, we plan to address the osteodifferentiation potential of hESC-OPs cocultured with vascular cells within 3D scaffolds to generate vascularized bone tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cells were dissociated into single cells with TrypLE™/Accutase, and stained directly with conjugated antibodies (Table S2, Supporting Information) according to the manufacturer's instruction . Stained cells were analyzed with BD LSRFortessa (Becton Dickinson) and FlowJo software.…”
Section: Methodsmentioning
confidence: 99%
“…The immunoregulatory effects of stem cells make them a promising therapy for periodontitis. Although several reports have indicated that the stem cells mentioned above can be delivered into infectious sites and function as critical players in the control of inflammation and the regulation of immune responses to achieve regeneration in models of periodontitis, the immunomodulatory capabilities of these cells have not entirely been elucidated [ 137 , 138 ]. Moreover, evidence of stem cell-mediated immunomodulation is limited both in vitro and in vivo .…”
Section: Conclusion Future Clinical Application and Challengesmentioning
confidence: 99%